Prevalence of excessive body fat among adolescents of a south Brazilian metropolitan region and State capital, associated risk factors, and consequences - Leandra Ulbricht; Mariane Ferreira de Campos; Eduardo Esmanhoto; Wagner Luis Ripka (BMC, 2018)
Abstract Background The prevalence of overweight/obesity has become a major concern for public health in developing countries. Risk factors need to be well documented so that these countries develop public policies to fight the problem. Thus, the objective of this study is to determine the prevalence of excess fat among adolescents of a South Brazilian State Capital associated with risk factors and their consequences. Methods This study was conducted between 2014 and 2016 with adolescents aged 11-18 years. The following body composition measurements were collected: body mass, height, waist circumference, fat mass and bone mineral density (this latter through dual energy X-ray absorptiometry). Biochemical data as glucose, total cholesterol, and triglycerides were also collected. Finally, socioeconomic questionnaires were applied, as well as questionnaires regarding: the education level of guardians, active transportation, time spent with sedentary activities and physical activities. Odds ratios and chi-square test were applied in statistical analysis. Results Data from 675 adolescents, from which 70% were males, were analyzed. The mean age was 14.7 ± 1.8 years. The prevalence of excess fat was 18.2% in boys and 92.1% in girls. As for sedentary lifestyle and physical inactivity, having one of these factors increased the risk of being overweight by 7.9 times for boys and 3.0 times for girls. In boys, there was a significant association between excess fat and waist circumference (p = 0.000; OR = 13.5; CI = 7.0-25.9), physical activity level (p = 0.000; OR = 4.0; CI = 2.5-6.5), triglycerides (p = 0.019; OR = 2.2; CI = 1.1-4.2) and total cholesterol (p = 0.000; OR = 2.6; CI = 1.6-4.5). In girls, there was an association between having excess fat and an increase in total cholesterol (p = 0.000; OR = 8.0; CI = 2.6-24.4). Conclusions The high prevalence of excess fat was greater than what was described by some studies conducted in developed countries. This reality demonstrates the need to implement public policies that can directly promote the reduction of sedentary habits and reinforce the importance of adopting an active lifestyle.